2013
DOI: 10.1152/ajprenal.00090.2013
|View full text |Cite
|
Sign up to set email alerts
|

Role of the endogenous opioid system in modulation of urinary bladder activity by spinal nerve stimulation

Abstract: The role of the endogenous opioid system in modulation of urinary bladder activity by spinal nerve (SN) stimulation was studied in anesthetized female rats, using the rat model of isovolumetric bladder contraction. SN stimulation at a fixed frequency of 10 Hz attenuated bladder contraction frequency; the magnitude of the inhibition was directly proportional to the current intensity. Neither the κ-opioid antagonist nor-binaltorphimine (2 mg/kg iv) nor the δ-opioid antagonist naltrindole (5 mg/kg iv) attenuated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Recently, an important role of naloxone-sensitive m ORs was also identified in sacral neuromodulation of isovolumetric bladder contractions in rats (Su et al, 2013). In these experiments, the effect of sacral neuromodulation was not altered by norbinaltorphimine (2.0 mg/kg i.v.)…”
Section: Discussionmentioning
confidence: 80%
“…Recently, an important role of naloxone-sensitive m ORs was also identified in sacral neuromodulation of isovolumetric bladder contractions in rats (Su et al, 2013). In these experiments, the effect of sacral neuromodulation was not altered by norbinaltorphimine (2.0 mg/kg i.v.)…”
Section: Discussionmentioning
confidence: 80%
“…A recent study in rats has also shown that μ ‐opioid receptors are involved in sacral neuromodulation of bladder activity (Su et al. ). In addition, whether these neurotransmitters play different roles in acute‐ and post‐TNS inhibition also needs to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…One would assume that output signals would be synchronized if the perfectly matched pulses from right and left SN stimulation are transmitted directly. Therefore enhanced bladder inhibitory effects to bilateral stimulation could be attributed to a polysynaptic reflex at the spinal and supraspinal centers [20]. …”
Section: Discussionmentioning
confidence: 99%